Creative tourism as a challenging proposal for peripheral territories: insights from an ongoing case study in Portugal - Perestrelo, Margarida; Costa, P.; Gato, M. A.; Cruz, A. R.; Tomaz, E. (59th ERSA Congress “Cities, regions and digital transformations: Opportunities, risks and challenges”, 2019)
In many countries around the world, the tourism sector has been gaining particular relevance in the development of several cities and regions. However, it has also been raising several concerns about the negative impacts of the growth of these activities. In Portugal, several cities seek to benefit from the wave of tourist attractiveness that has been projecting the country in several international rankings. At the same time, rural areas and small sized cities try to find new tourist products as alternatives to counter the congestion and massification problems of the large metropolis tourism activity by developing creative initiatives based on tangible and intangible local projects. For peripheral territories, such as rural areas or small sized cities, investing on creative-based tourism as a wide process involving artistic creation and the co-creation or accumulation of aesthetic and symbolic knowledge can be a good and complementary strategy for territorial enhancement. From a planning perspective, the idea of linking creative dynamics and tourism is generally supported by arguments such as: an opportunity for territorial, economic and social regeneration to diversify the structure of the tourism sector; to retain population and revitalize their cultural and social heritage; to enhance creative milieus and foster organic territorial dynamics, reflecting the “sense of place” and the unique and intangible characteristics of local communities (Richards & Wilson, 2006). Thus, there is a growing interest in understanding how cultural and creative activities can drive the development of innovative and sustainable tourism solutions. The way tourists can be embedded in the local cultures to find out about place identities and explore the authenticity of local intangible heritage highlights the role of tourists as co-creators of knowledge and co-producers of experiences (Binkhorst, 2007), but also the active role that the host communities can (and should) play in the process. Taking the CREATOUR project as an example — a project currently being implemented at national level in Portugal (Norte, Centro, Alentejo, and Algarve NUTS II regions) that aims to develop and pilot an integrated approach and research agenda for creative-based tourism in small cities and rural areas – this communication intends to present some results of this pioneering experience. The discussion will focus on the challenges of the co-creation process of places and cultural experiences and some expected impacts induced on territories and local communities where the creative-based tourism activities are being implemented.